Analisis Perbedaan Antropometri Vertebra Thorax (T12) Antara Pria dan Wanita dengan Menggunakan Image CT Scan 3D : Pendekatan Teknik Geometric Morphometric - Ghiffari Satrya Pratama; Afiana Rohmani; Arief Tajally (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
The determination of human skeletons and fragments has significant value from both a legal and humanitarian perspective, which generally includes the evaluation of teeth, bones, fingerprints, and genetic material. However, fingerprinting and DNA methods are not without their limitations. Sex determination is an important first step in biological profiling, which plays a role in victim matching. Research on sex identification using T12 vertebrae with Geometric Morphometric (GM) techniques is still relatively rare. The GM technique deeply explores the dimensions and shape of objects. This study used an analytic observational design with a retrospective cross-sectional approach, involving 100 CT scan samples from Dr. Kariadi Hospital. Gender was used as the independent variable, while size (centroid size) and shape (principal component) were the dependent variables. The results of independent t-test and Mann-Whitney analysis showed a significant difference in T12 vertebra size between men and women (p = 0.000), but not in shape (p = 0.439). Based on the GM technique, it was revealed that the difference in T12 vertebrae between men and women was in size, not shape.